Singing the Himalayan crossroads traditional songs of Ladakh - Dinnerstein, Noé (Albany State University of New York Press, 2025)
"Introduces the traditional songs of Himalayan Ladakh through their history, ethnology, poetry, and Tibetan Buddhism beliefs"--
A Cultural and Historical Overview of Ladakh -- Buddhism in Ladakhi Traditional Songs -- Music in Muslim Communities -- Music in a Changing Society -- Songs and Cultural Representation in the Modern Market -- Other Song Genres -- Musical Characteristics of Traditional Ladakhi Song -- Concluding Summary.
Includes bibliographical references and index
Keywords: Gesar; Folk songs, Ladakhi -- History and criticism; Songs, Ladakhi -- History and criticism; Music -- India -- Ladākh -- History and criticism; Music -- India -- Ladākh -- Analysis, appreciation; Music -- Social aspects -- India -- Ladākh; Music -- Religious aspects -- India -- Ladākh; Music -- Religious aspects -- Buddhism